Attack of an infant by a female in a troop of howler monkeys (Alouatta pigra) - Parsons, James; Svensson, Magdalena S. (Neotropical Primates, 2021)
Within the New World primate family of Atelidae, infanticidal attacks are most commonly reported in howler monkeys (Alouatta spp., Crockett, 2003; Knopff et al., 2004; Aguiar et al., 2005; Agoramoorthy and Rudran, 2009; Van Belle et al., 2010; Pavé et al., 2012). The howler monkey species that have been observed to exhibit this behaviour are black and gold howler monkeys (Alouatta caraya, Crockett, 2003; Pavé et al., 2012); Colombian red howler monkeys (A. seniculus, Agoramoorthy and Rudran, 1995; Beltrán and Stevenson, 2012); mantled howler monkeys (A. palliata, Crockett, 2003); brown howler monkeys (Martins et al., 2015); and Yucatán black howler monkeys (A. pigra, Crockett, 2003; Van Belle et al., 2010). In these documented attacks there is a lack of detail regarding the involvement of females, as the male is usually identified as the aggressor. These attacks are likely to occur following the immigration of a new male to a troop (Van Belle et al., 2010; Beltrán and Stevenson, 2012), up to five months after taking over a troop (Agoramoorthy and Rudran, 2009). A majority of infanticidal attacks in howler monkeys involve assumed unrelated assailant and victim, therefore these instances align with the sexual selection hypothesis (Hrdy, 1979).